Pengaruh Pengelolaan Keuangan Daerah, Sistem Akuntansi Keuangan Daerah dan Kompetensi Sumber Daya Manusia terhadap Kualitas Laporan Keuangan Pemerintah Daerah pada Badan Keuangan dan Aset Daerah Kab. TTU - Carolin Stephanie Serafin Meko; Maria Prudensiana Leda Muga; Novi Theresia Kiak (International Forum of Researchers and Lecturers, 2024)
This research aims to determine the influence of regional financial management, regional financial accounting systems, and human resource competence on the quality of regional government financial reports in TTU Regency, partially or simultaneously. This research uses a quantitative research approach. This research uses primary data. The sampling technique in this research was purposive sampling with respondents consisting of 36 respondents who were at the Regional Financial and Asset Agency in TTU Regency. Where data is collected through questionnaires distributed, and the analysis is based on respondents' answers obtained through questionnaires distributed by researchers. The data analysis technique uses multiple linear regression analysis with the help of the SPSS 25 program. The results of this study state that regional financial management does not have a significant effect on the quality of financial reports, while the regional financial accounting system and human resource competency have a significant effect on the quality of regional government financial reports, and of the three regional financial management variables, the regional financial accounting system and human resource competency together have a significant effect on the quality of regional government financial reports.